2017
DOI: 10.1002/jemt.22877
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metals cadmium and chromium alone and in combination on the liver and kidney tissue of male Spraque‐Dawley rats: An ultrastructural and electron‐energy‐loss spectroscopy investigation

Abstract: Heavy metal pollution has increased in the last decades. Water sources are contaminated and human exposure is often long term exposure to variable amounts of different metals. In this study, male Sprague-Dawley rats were exposed via oral gavage for 28 days to cadmium (Cd) and chromium (Cr), alone and in combination at concentrations 1000 times the human World Health Organization's acceptable water limits. Rat equivalent dosages were used. Blood markers of liver and kidney function were measured, changes to cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…This was in line with proven literature evidence of alteration of renal functions caused by Cr. The rise in these parameters was due to loss of functional integrity in the kidney and renal tubule distortion as a consequence of Cr administration (Venter et al, 2017). Many studies were in line with our findings and clarified that Cr-induced renal dysfunction could be due to Cr renal tubular damage and cell debris obstruction (Sahu et al, 2014;Hegazy et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…This was in line with proven literature evidence of alteration of renal functions caused by Cr. The rise in these parameters was due to loss of functional integrity in the kidney and renal tubule distortion as a consequence of Cr administration (Venter et al, 2017). Many studies were in line with our findings and clarified that Cr-induced renal dysfunction could be due to Cr renal tubular damage and cell debris obstruction (Sahu et al, 2014;Hegazy et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…Various ultrastructure anomalies in the testicular cells were observed in the NiO-NPs-treated group, including anatomical alterations in the nucleus and cytoplasm in almost all the spermatogenic stages. These anomalies are a consequence of DNA and protein damage, as well as impairment of membranes due to the action of a xenobiotic (Bertin and Averbeck, 2006;Venter et al, 2017). Metals can change the structure of membranous organelles such as the mitochondria and endoplasmic reticulum, as well as plasma and nuclear membranes nu binding to membranes and DNA-associated proteins (Venter et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As to the cells of the proximal tubule, in CdCl 2 -challenged mouse lysosomes and myelin bodies, distorted or ring-shaped mitochondria, cytoplasmic vacuolization or cytolysis [ 13 ], decreased, irregular microvilli [ 16 ], fragmented and short basolateral invaginations [ 15 ], and condensed chromatin [ 17 ] have been described.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, damaged liver cells release a Cd-metallothionein (MT) complex which is filtered from the glomerulus and then endocytosed by the cells of the proximal tubule, where it is degraded by lysosomes: in this way, free Cd is released in the tubules [ 10 ], where 99% of the filtered Cd is reabsorbed [ 11 ], resulting in accumulation and consequent nephrotoxicity. In particular, it was demonstrated that the target sites of Cd are the proximal tubules [ 12 ]; in these structures, lesions of the brush border and fragmentation of the epithelial cells with the granular cytoplasm were observed [ 13 17 ]. However, Cd-induced structural damages of the glomeruli [ 18 ], consisting in increased mesangial matrix, glomerular swelling, and increased urinary space, were also demonstrated [ 19 ].…”
Section: Introductionmentioning
confidence: 99%